Pregnancy and weight gain: a scoping review of women’s perceptions and experiences with stigma - Hima Sasidharan; Ashruti Bhatt; Manasee Mishra (BMC Pregnancy and Childbirth)
Abstract Background Weight stigma can impact any woman who considers herself as overweight, regardless of BMI. Pregnant women are at risk of experiencing stigma related to weight which harm their physical and mental health. To support and guide on healthy weight gain during pregnancy, it is important to explore women’s perceptions and experiences of weight related stigma. This can inform programs and policies to improve maternal and child health outcomes. A scoping review on this issue will provide valuable insights, identify gaps in current research, and establish a foundation for informed interventions. Methods A search syntax was created to retrieve the relevant results from PubMed and Google Scholar. A scoping review was undertaken of published peer reviewed research indexed in these databases, which were written in English, and focused only on primary studies. The methodology for this scoping review was based on the framework proposed by Arksey and O'Malley (2005) and the subsequent recommendations provided by Levac et al. (2010). Results From a total of 3109 articles identified using search terms, 85 articles were included for review. There are four themes in this scoping review: pregnant women’s perceptions and experience with healthcare givers; pregnant women’s experience with family and friends; pregnant women’s experience with other members of society; and pregnant women’s experience with the media. Weight stigmatization can hinder the communication between healthcare providers and women leading to misunderstanding and compromising the quality of care. This can prevent women from seeking necessary care. Stigmatizing behavior of friends, family and the perpetuation of stigma in the media influences how women perceive their pregnancy weight gain, intensifies feelings of shame, isolation and negatively impacts women’s mental well-being and body image during pregnancy. Conclusion This scoping review examines the perceptions and experiences of weight stigma among pregnant women, focusing on their interactions with healthcare providers, family and friends, other members of society and stigma perpetuated by the media. The review gives an insight into how weight stigma can heighten women’s stress and also leads to the avoidance of essential medical care, which affect the health of both the mother and the child. Addressing stigma from various sources is crucial for the general well-being and health of both women and children.